O origami e suas dobras no ensino e aprendizagem de conteúdos matemáticos - Fleischmann, Scheila Odisi (2019)
We present in this work the paper folding technique, origami, applying Huzita-Hatori axioms, Haga theorems and Fujimoto approximations for fractions of type 1=n. After a diagnostic research with elementary and high school students of a public school in the State of Santa Catarina, we developed with these students workshops introducing origami with applications in the golden rectangle and in the study of fractions, among others. The works from these workshops were presented at a Knowledge Fair, obtaining the first place in the High School category. We conclude that origami workshops allow, under different approaches, the presentation and discussion of a variety of contents that allow the deepening of mathematical knowledge.